A new class of quadruplex DNA-binding nickel Schiff base complexes. Issue 15 (27th March 2020) - Pham, Son Q. T.; Assadawi, Nawal; Wells, Jadon; Sophocleous, Reece A.; Davis, Kimberley J.; Yu, Haibo; Sluyter, Ronald; Dillon, Carolyn T.; Kelso, Celine; Beck, Jennifer L.; Willis, Anthony C.; Richardson, Christopher; et al.
Abstract : A new nickel Schiff base complex shows selective binding behaviour towards quadruplex DNA and cytotoxicity against cancer cells. Abstract : We have prepared six new nickel Schiff base complexes via reactions of substituted benzophenones with different diamines in the presence of nickel(ii ). These new complexes were then reacted with 1-(2-choroethyl)piperidine to afford a further six novel nickel(ii ) Schiff base complexes bearing pendant ethylpiperidine groups. The complexes bearing the ethylpiperidine moieties had greater solubility in water, and were therefore suitable for use in DNA binding experiments. ESI mass spectra of solutions containing 4 and the parallel, tetramolecular quadruplex Q4, contained ions attributable to formation of non-covalent complexes. In contrast, no ions from non-covalent complexes were observed when the experiments were repeated using 4 and either a double stranded DNA (dsDNA) molecule (D2), or parallel Q1, a unimolecular quadruplex DNA (qDNA). The ESI-MS binding study also revealed that 14 has a significant ability to form non-covalent complexes with qDNA, but does not interact to the same extent with D2. This is supported by the large changes to the ellipticity of bands observed in the circular dichroism spectra of two different unimolecular qDNA molecules ( c-kit 1 and Q1), including the latter annealed under conditions designed to induce formation of alternative topologies (antiparallel and hybrid). In Fluorescent Indicator Displacement (FID) assays conducted using the new nickel complexes, 14 gave the lowest values of DC50 for experiments conducted with Q1 and Q4. Furthermore, 14 showed greater stabilisation of an antiparallel qDNA molecule in FRET assays than when the other new complexes were examined. These results highlight the potential of 14 as a lead complex for future structure/DNA binding investigations. This is reinforced by the results obtained from cytotoxicity studies performed using four of the nickel complexes, including 14, and Chinese hamster lung cancer (V79) cells, which gave IC50 values between 4 and 12 μM. These complexes were also shown to have the ability to induce apoptosis in the same cancer cell line.